Integration Of Tree Planting In Family-Based Social Forestry As An Effective Tool For The Conservation Of Endangered Timber Species For Kingdom Of Cambodia - Chea, Sam Ang (2013)
Combadian has experiences deforestation and forest degradation since late 1990s due to rapid economic development and fast growing population. As a reult, timber species are now under the endangered list. The conservation of these timbers is given higher priority. In this project, Thress villages in the provience of rattanakiri were selected.